Pengembangan Bahan Ajar E-Handout Bahasa Indonesia untuk Meningkatkan Motivasi Belajar Siswa di Sekolah - Mira Sefriyani Laoli; Jessica Nurniat Zebua; Nelvan Putra Hulu; Lestari Waruwu (Journal on Education, 2023)
The aims of this study were: (1) to determine the process of developing E-Handout teaching materials for Indonesian subjects, (2) to determine the level of effectiveness of E-Handout teaching materials in the learning process, (3) to determine the validity and reliability of the effectiveness of E-Handout teaching materials Handout, (4) knowing the level of students' motivation in learning. This research is Development Research (R&D). After the teaching materials were prepared by the researcher, several steps were carried out, including: Testing the validity of the material, the validity of the language, and the validity of the design. Based on the research findings, product trials involving subject matter experts yielded an average score of 91% with Very Eligible criteria, while trials involving linguists produced an average score of 98.8% with Very Eligible criteria. Product trials involving design expert validators also resulted in an average score of 98.8% with Very Eligible criteria. Then the results of testing the effectiveness of the E-Handout teaching materials to students were 32 students with a percentage of 96.01% with the criteria, and based on the test results using the SPSS 17.0 For Windows application, all statement items are valid, which means r count > r-table with probability Bartlents test sig 0.000 (0.000 <0.05) and questionnaire reliability test on the effectiveness of E-Handout teaching materials with SPSS 17.0 For Windows in the Reliability Statistics column with a Cronbach's Alpha value of 0.763 (0.763> 0.6), thus it can be concluded that Material Development Teaching Indonesian E-Handout to Increase Student Learning Motivation in Schools is very practical and feasible to use.